2020
DOI: 10.3390/foods9060773
|View full text |Cite
|
Sign up to set email alerts
|

Acacia Polyphenol Ameliorates Atopic Dermatitis in Trimellitic Anhydride-Induced Model Mice via Changes in the Gut Microbiota

Abstract: We have previously shown that acacia polyphenol (AP), which was extracted from the bark of Acacia mearnsii De Wild, exerts antiobesity, antidiabetic, and antihypertensive effects. In this study, we examined the effect of AP on atopic dermatitis. Trimellitic anhydride (TMA) was applied to the ears of mice to create model mice with atopic dermatitis. The frequency of scratching behavior in the TMA-treated group was significantly higher than that in the control group, and the expression levels of inflammatory mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In this study, the mice were sensitized and challenged with OVA to establish an AD model as observed in a previous report [ 30 ]. Administration of a probiotic mixture to the mice inhibited the development of skin lesions and scratching behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the mice were sensitized and challenged with OVA to establish an AD model as observed in a previous report [ 30 ]. Administration of a probiotic mixture to the mice inhibited the development of skin lesions and scratching behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in the gut microbiota are associated with the induction of several diseases and are strongly linked to the development of atopic disorders, including food allergies [ 4 , 35 , 36 ]. In line with the hygiene hypothesis, a reduced or altered microbial load may insufficiently counterbalance the Th2 response, thus favoring the occurrence of food allergies [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…and Lactobacillus spp. in the intestine was observed after administration of acacia extract [ 66 ]. Sargassum horneri is an edible brown alga known for its beneficial biological properties, including anti-inflammatory properties.…”
Section: Dietmentioning
confidence: 99%